2013
DOI: 10.4314/ajpsy.v16i5.48
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psycho-social profile of child and adolescent mental health care users and services at an urban child mental health clinic in South Africa

Abstract: Objective: National and international child and adolescent mental healthcare policy and action advocate that the health and well being of children should be increasingly given greater attention. The purpose of this study was to describe the demographic, socio economic and clinical profile of the users at the child and adolescent mental health clinic of the Rahima Moosa Mother and Child Hospital (RMMCH). Method: A descriptive, retrospective clinical audit from users' clinical files was performed over a one-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
6
11
0
1
Order By: Relevance
“…This observation is similar to findings in child psychiatry clinic populations in South Africa and the United States of America [19, 20]. Epidemiological studies reveal a preponderance of depression in females around the age of 13 years resulting in the increased proportion of girls in mental health facilities [21], a finding that was consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is similar to findings in child psychiatry clinic populations in South Africa and the United States of America [19, 20]. Epidemiological studies reveal a preponderance of depression in females around the age of 13 years resulting in the increased proportion of girls in mental health facilities [21], a finding that was consistent with the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies in Africa among same aged post-secondary students produced similar findings, suggesting that test-taking and performance-based stress can increase young adults' odds for depression (Khasakhala et al, 2012;Raman and Janse van Rensburg, 2013). Students in the later stages of their education are likely to be undertaking competitive examinations that determine admission to highly competitive tertiary institutions.…”
Section: Patterns Of Misclassificationsupporting
confidence: 60%
“…The inattention, impulsivity and hyperactivity which are the symptoms of ADHD are usually evident in the classroom, placing teachers in a unique position to identify and refer such students for further assessment [3]. Despite this, studies have found that teachers have limited and inaccurate knowledge about ADHD and often provide inappropriate information about the condition to parents [4].…”
Section: Introductionmentioning
confidence: 99%